Self-healing of structural carbon fibres in polymer composites. Issue 1 (1st January 2020) - Wang, Yongjing; Edgell, Jake; Graham, Nicholas; Jackson, Nathaniel; Liang, Hengkun; Pham, Duc Truong
Abstract: Carbon fibre–reinforced composites (CFRCs) are increasingly used in aeroplanes, satellites and offshore wind turbines. Access those systems for repair when the material is damaged may be difficult. Researchers have incorporated vascular systems containing healing agents into CFRCs, enabling them automatically to recover from delamination and debonding. However, self-recovery of the structural fibres that give CFRCs their exceptional mechanical properties is still impossible. This paper describes a method to make CFRCs self-heal following structural fibres' damage. This involves automatically delivering epoxy-based healing agents containing short carbon fibres (SCFs) to cracks through an embedded vascular system. Cracks are created by disk-cutting through the carbon fibre layer of CFRC specimens. The SCFs in the released healing agents can be aligned in a local electric field produced by applying a potential to the broken structural carbon fibres. The alignment reconnects the structural carbon fibres. Process parameters were investigated to observe their effects on the healing performance and determine the optimum healing agent composition and conditions. In comparison to using conventional healing agents without SCFs and electric alignment which restored 25.2% of a CFRC's original strength, employing the proposed approach increased the recovery to 47.3%.